A binder for powder injection molding process and its preparation method and application

By modifying bisphenol A epoxy resin with polydimethylsiloxane-compatible adhesives and mold coatings, the problems of flash and insufficient mechanical strength in the powder injection molding process were solved, and efficient demolding and high-quality embryo production were achieved.

CN120438605BActive Publication Date: 2025-09-16HEFEI HUIZHI NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510939872.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-09
Publication Date
2025-09-16
Estimated Expiration
2045-07-09

AI Technical Summary

Technical Problem

In the powder injection molding process, improper temperature and pressure cause the molded body to separate along the parting line, generating flash that needs to be removed manually. In addition, the mechanical strength of the injected blank is insufficient, affecting production efficiency and yield rate.

Method used

A modified bisphenol A epoxy resin and a polydimethylsiloxane-compatible adhesive are used to form a low surface energy coating on the mold surface to improve bonding and demoulding properties.

Benefits of technology

It improves the mechanical strength and demoulding performance of the injection molded product, reduces flash, and improves production efficiency and mold body quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention belongs to the technical field of adhesives, and specifically belongs to an adhesive for powder injection molding process and its preparation method and application. Raw materials: paraffin wax, stearic acid, polyethylene glycol, polydimethylsiloxane, ethyl acetate solution, modified bisphenol A epoxy resin; modified bisphenol A epoxy resin is prepared from methoxy polyethylene glycol amine and bisphenol A epoxy resin. Paraffin wax is added to polyethylene glycol solution, mixed evenly, and then stearic acid is added, heated and stirred to obtain mixed solution one; polydimethylsiloxane and modified bisphenol A epoxy resin are added to ethyl acetate solution, mixed evenly, and then heated and stirred to obtain mixed solution two; mixed solution one and mixed solution two are mixed, heated and stirred, and then discharged, cooled, filtered, and an adhesive is obtained. The adhesive is used in powder injection molding process. The adhesive provided by the present invention can make the injection blank have good forming performance and better mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adhesives, and in particular to an adhesive for a powder injection molding process and a preparation method and application thereof. Background Art

[0002] Powder injection molding (PIM) uses injection molding to fill a mold cavity with material, creating parts with complex structural features in a single step. Compared to traditional machining and precision casting, this process reduces the number of steps, simplifies the manufacturing process, and improves manufacturing efficiency.

[0003] During the powder injection molding process for complex parts, improper temperature and pressure conditions can cause the preform to separate along the parting line, resulting in flash that must be manually removed with a soft brush. Furthermore, to meet mold design requirements, the preform may contain excess structure that must be manually removed with a sharp tool. However, during manual processing, using a brush to remove flash and excessive force can cause deformation of the preform, reducing the number of good parts and lowering production efficiency.

[0004] Therefore, effectively improving the mechanical strength of injection molding has positive production significance. Summary of the Invention

[0005] In order to solve the technical problems in the prior art, the present invention provides an adhesive for a powder injection molding process and a preparation method and application thereof.

[0006] The technical solutions of the present invention include the following:

[0007] In the first aspect, an adhesive for powder injection molding process is prepared from the following components in parts by weight: 20-23 parts of paraffin wax, 5-8 parts of stearic acid, 15-20 parts of polyethylene glycol, 10-15 parts of polydimethylsiloxane, 25-30 parts of ethyl acetate solution, and 10-15 parts of modified bisphenol A epoxy resin; wherein the modified bisphenol A epoxy resin is prepared from methoxy polyethylene glycol amine and bisphenol A epoxy resin.

[0008] Preferably, the preparation method of the modified bisphenol A epoxy resin comprises the following steps:

[0009] The bisphenol A epoxy resin is heated and melted, and then methoxy polyethylene glycol amine and a catalyst are added, and the mixture is heated and reacted under a nitrogen atmosphere. After the reaction, the mixture is cooled to room temperature and washed to obtain a modified bisphenol A epoxy resin.

[0010] Preferably, the heating temperature of the blend is 100-150° C., the mass ratio of bisphenol A epoxy resin to methoxy polyethylene glycol amine is 3-9:1, the catalyst includes tetraisopropyl titanate, and the reaction is carried out under N2 atmosphere for 5-10 hours.

[0011] Preferably, the bisphenol A type epoxy resin includes DGEBA, and the molecular weight of the methoxy polyethylene glycol amine is 2000.

[0012] In a second aspect, the aforementioned method for preparing an adhesive for use in a powder injection molding process comprises the following steps:

[0013] Weigh each component by weight, add paraffin wax to the polyethylene glycol solution, mix well, add stearic acid, heat and stir to obtain a mixed solution 1;

[0014] Adding polydimethylsiloxane and modified bisphenol A epoxy resin into ethyl acetate solution, mixing evenly, and then heating and stirring to obtain a second mixed solution;

[0015] The mixed solution 1 and the mixed solution 2 are mixed, heated and stirred, discharged, cooled, and filtered to obtain an adhesive for powder injection molding technology.

[0016] Preferably, the heating temperature is 80-110° C. and the stirring time is 1-6 h.

[0017] In a third aspect, an adhesive is used in a powder injection molding process, wherein the adhesive is one of the aforementioned adhesives for use in a powder injection molding process or is prepared according to the aforementioned method for preparing an adhesive for use in a powder injection molding process, comprising the following steps:

[0018] The metal powder is mixed with the binder to obtain the feed material, which is then granulated and then injection molded. The mold is preheated first, the feed material is injected into the mold, and the mold is integrally formed. After cooling, the mold is demolded to obtain a blank. The blank is degreased, sintered, and cooled to obtain a formed blank.

[0019] Preferably, the mold is a mold with a coating or a mold without a coating, and the coating is formed by a coating liquid. The preparation method of the coating liquid comprises the following steps: adding TEOS to anhydrous ethanol, adding deionized water dropwise, and adjusting the pH to 4-5; stirring the reaction to obtain a sol liquid, diluting the fluoroamide silane monomer and the aminosilane oligomer with isopropanol, and then adding a surfactant and ultrasonically dispersing; adding the sol liquid while stirring, and finally adding an organic metal catalyst, stirring evenly, to obtain a coating liquid.

[0020] Preferably, the preparation method of the fluoroamide silane monomer comprises the following steps: dissolving APTES in anhydrous THF, cooling in an ice bath to 0-5°C, adding tetrafluorosuccinyl chloride dropwise, maintaining the temperature ≤10°C, continuing to stir after the addition is completed, then adding triethylamine dropwise, heating and stirring to obtain a reaction solution, extracting the reaction solution, drying the organic phase, filtering, and vacuum rotary evaporation to obtain the fluoroamide silane monomer.

[0021] Preferably, the surfactant includes an organosilicon surfactant, the organometallic catalyst includes an organobismuth catalyst and an organotin catalyst, and the organotin catalyst includes at least one of dibutyltin dilaurate and dibutyltin diacetate.

[0022] Preferably, the coating is formed by a coating liquid, which is sprayed or brushed on the area of ​​the mold where it will be demolded later, with the coating thickness controlled to be 3-5 μm. The coating is left to dry on the surface; the mold is then placed in a heating box at 100-150° C. for insulation; the temperature is then slowly raised to 150-200° C. and then maintained for insulation to obtain a mold with a coating.

[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0024] Improved mechanical strength and structural stability of the blank: The bisphenol A epoxy resin used in the present invention is a high-performance thermosetting resin. It is widely used in many industrial fields because of its good bonding properties and versatility of formula. The polydimethylsiloxane used has the characteristics of small viscosity change with temperature and excellent lubricity, which is helpful for demolding during powder injection molding. However, since the solubility parameters of the two are too different, they are not compatible. Through grafting modification, the modified bisphenol A epoxy resin and polydimethylsiloxane have good compatibility. Adding polydimethylsiloxane to bisphenol A epoxy resin can effectively improve the bonding properties of the adhesive, thereby improving the mechanical strength of the injection blank.

[0025] Improved mold demoulding performance and reduced demoulding resistance: The coating liquid prepared by the present invention forms a dense and low-surface-energy coating interface on the mold surface, effectively reducing the demoulding force between the mold and the blank, reducing flash, avoiding structural defects caused by forced demoulding, and improving the quality and mechanical strength of the blank. DETAILED DESCRIPTION

[0026] To make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described below in conjunction with specific embodiments. The methods described are conventional methods unless otherwise specified, and the raw materials described can be obtained from public commercial channels unless otherwise specified.

[0027] Example 1

[0028] Preparation of modified bisphenol A epoxy resin, the specific steps are as follows:

[0029] Prepare the raw materials: Bisphenol A epoxy resin is DGEBA (bisphenol A diglycidyl ether). The molecular weight of methoxy polyethylene glycol amine is 2000.

[0030] 180g of bisphenol A epoxy resin was placed in a three-necked round-bottom flask equipped with a reflux condenser, a mechanical stirrer, and a thermometer. The bisphenol A epoxy resin was heated until it melted. 30g of methoxypolyethylene glycolamine and 0.15g of tetraisopropyl titanate (TPT) were then added. The mixture was heated to 130°C and reacted under a nitrogen atmosphere for 7 hours. After the reaction, the mixture was cooled to room temperature and washed with toluene to remove unreacted methoxypolyethylene glycolamine, resulting in a modified bisphenol A epoxy resin.

[0031] The reaction process is as follows:

[0032]

[0033] It is worth noting that the bisphenol A epoxy resin used in the present invention is a high-performance thermosetting resin and is widely used in many industrial fields because of its good bonding properties and the versatility of its formula. The polydimethylsiloxane used has the characteristics of little viscosity change with temperature and excellent lubricity, which helps to facilitate demoulding during powder injection molding. However, since the solubility parameters of the two are too different, they are not compatible. Through the method of graft modification, the modified bisphenol A epoxy resin and polydimethylsiloxane have good compatibility. Adding polydimethylsiloxane to bisphenol A epoxy resin can effectively improve the bonding properties of the binder, thereby improving the mechanical strength of the injection molded blank.

[0034] Example 2

[0035] A method for preparing an adhesive for a powder injection molding process, comprising the following steps:

[0036] S1. Weigh the components in parts by weight, add 22 parts of paraffin wax to 18 parts of polyethylene glycol solution, mix well, add 6 parts of stearic acid, heat and stir at 80 ° C for 4-5h to obtain a mixed solution;

[0037] S2. 12 parts of polydimethylsiloxane and 13 parts of the modified bisphenol A epoxy resin prepared in Example 1 were added to 28 parts of ethyl acetate solution, mixed and heated at 95 ° C with stirring for 1-2h to obtain a mixture of the second;

[0038] S3. The mixed solution obtained in step S1 and the mixed solution obtained in step S2 were mixed, heated at 90°C with stirring for 2-3h, discharged, cooled to room temperature, and filtered with a 200-mesh sieve to obtain an adhesive for powder injection molding technology.

[0039] The adhesive for the powder injection molding process provided by the present invention can ensure that the injection blank has good molding performance and good mechanical strength.

[0040] The applications of adhesives are given below:

[0041] Example 3

[0042] Prepare the following raw materials: hydroxy-terminated polydimethylsiloxane (PDMS-OH) with a molecular weight of Mn~1500, aminosilane oligomer Dynasylan® 1146 from Evonik, surfactant BYK-3455, catalyst dibutyltin dilaurate, and all other raw materials of analytical grade.

[0043] Preparation of sol solution: Add 15g of TEOS (tetraethyl orthosilicate) to 60g of anhydrous ethanol; slowly add 5g of deionized water dropwise, and then add acetic acid dropwise to adjust the pH to 4-5; stir and react at room temperature for 3h to obtain a sol solution.

[0044] Preparation of fluoroamide silane monomer: Dissolve 10g of APTES (3-aminopropyltriethoxysilane) in 100mL of anhydrous THF (tetrahydrofuran) and cool to 0-5°C in an ice bath. Slowly add 7.8g of tetrafluorosuccinyl chloride dropwise, maintaining the temperature ≤10°C. Continue stirring for 1h after the addition is complete. Then, add 5g of triethylamine dropwise, warm to room temperature and stir for 2h to obtain a reaction solution. The reaction solution is washed with 50mL of 5% dilute hydrochloric acid, 50mL of saturated NaHCO 3、 The mixture was extracted with 50 mL of saturated brine, and the organic phase was dried over anhydrous MgSO4, filtered, and then evaporated under reduced pressure at 60°C and 0.1 MPa to obtain fluoroamide silane monomer.

[0045] 50 g of hydroxy-terminated polydimethylsiloxane (PDMS-OH) was dissolved in 150 mL of anhydrous toluene, 0.3 g of tetraisopropyl titanate was added, and the mixture was heated to 110 ° C under nitrogen protection. 6.7 g of fluoroamide silane monomer was added dropwise, and the mixture was refluxed for 3.5 h. Water and alcohol were removed, and the mixture was cooled to 80 ° C. 3 g of hexamethyldisilazane (HMDS) was added and stirred for 0.5 h. Then, the mixture was evaporated under reduced pressure at 80 ° C and 0.09 MPa to obtain fluorine-modified PDMS.

[0046] Prepare the coating liquid: In a beaker, add 10g of fluorine-modified polydimethylsiloxane and 5g of aminosilane oligomer, dilute with 40mL of isopropanol, then add 0.3g of surfactant, and disperse evenly by ultrasonication for 10 minutes; slowly add 30g of sol solution while stirring, and finally add 0.15g of catalyst, stir evenly to obtain the coating liquid.

[0047] Example 4

[0048] After cleaning the mold, the coating liquid of Example 3 was evenly sprayed or brushed on the area of ​​the mold where it would be demolded later, with the coating thickness controlled to 3-5 μm. The coating was allowed to stand until the surface of the coating dried. The mold was then placed in a 120° C. heating oven and kept warm for 30 minutes. The temperature was then slowly raised to 180° C., kept warm for another 20 minutes, and cooled to obtain a coated mold.

[0049] It should be noted that during the powder injection molding process, flash or material seepage is most likely to occur in the mold parting line area, which can lead to defects in the green body and even affect the subsequent debinding and sintering quality. Therefore, molds with coatings are constructed to improve demolding quality.

[0050] In Example 3, a coating liquid was prepared. APTES was reacted with tetrafluorosuccinyl chloride to introduce fluorine segments (-CF2CF2-) and amide groups (-CONH-), forming a functionalized fluoroamide silane monomer. Under the catalysis of tetraisopropyl titanate, the fluoroamide silane monomer was copolymerized and condensed with PDMS-OH to produce a block copolymer structure containing PDMS in the backbone and fluorine-containing segments in the side chains. HMDS capping eliminated residual silanol groups and prevented excessive cross-linking during coating curing, which could lead to coating embrittlement.

[0051] The coating liquid gradually solidifies in the mold at different temperatures. At 120°C, the aminosilane hydrolyzes and condenses, forming an Fe-O-Si covalent anchoring layer with the iron atoms on the mold surface. When heated to 180°C, the silicate sol dehydrates to construct a three-dimensional SiO2 inorganic framework. Simultaneously, the titanium crosslinks in the fluorinated PDMS form ≡Si-O-Ti≡ bonds with the framework. During cooling, the fluoroamide side chains (-CO-CF2-CF2-CO-NH-) spontaneously migrate to the surface, forming a fluorine-rich layer. This results in a mold coating that is stably adhered, non-flaking, has low surface energy, and is easy to release.

[0052] Example 5

[0053] The specific steps for preparing injection blanks or formed embryos are as follows:

[0054] Raw materials were selected: the metal powder was 17-4PH stainless steel powder (particle size D50 = 15 μm), and the oxygen content was ≤ 800 ppm.

[0055] The metal powder and the binder prepared in Example 2 were added to an internal mixer in a weight ratio of 62:38 and mixed at 150°C and 40 rpm for 90 minutes to obtain a feed. The feed melt index (190°C / 2.16 kg) was 28 g / 10 min.

[0056] The feed material is granulated and then injection molded. The coated mold of Example 4 is used as the mold. The mold is preheated to 65°C, and the feed material is injected into the mold by a metal injection molding machine or an injection molding machine. The mold is integrally formed and demolded after cooling to obtain a embryo body. The injection temperature is 125°C, the injection pressure is 40 MPa, the holding time is 8 s, and the cooling time is 15 s.

[0057] The embryo body was placed in a degreasing furnace, soaked in a solvent for 8 hours, dried, heated to 300°C, kept warm for 1 hour in a N2 atmosphere, and then slowly cooled to complete degreasing to obtain a degreased embryo body; wherein the solvent was a mixed solvent of ethyl acetate and n-hexane with a volume ratio of 1:1.

[0058] The degreased body was sintered by heating the temperature from room temperature to 1320°C at a rate of 3°C / min; the body was kept at 1320°C for 2 hours, and then cooled to room temperature at a rate of 5°C / min to obtain a formed body.

[0059] Example 6

[0060] Different from Example 5, in this example, a mold without coating is used, and the rest is the same as Example 5.

[0061] Comparative Example 1

[0062] Raw material selection: Polypropylene granules are injection molding grade polypropylene, Exxon PP3546G can be selected.

[0063] Add 28 g of paraffin wax, 27 g of polypropylene particles, and 0.6 g of antioxidant 1010 into a beaker, heat in a 60°C water bath to a semi-molten state, mechanically stir for 5 minutes, cool to 50°C, add 3.6 g of stearic acid powder, and stir until completely dissolved to obtain an adhesive.

[0064] Comparative Example 2

[0065] In this comparative example, different from Example 5, the adhesive prepared in Example 2 was replaced with the adhesive of Comparative Example 1, and the rest was the same as Example 5.

[0066] Comparative Example 3

[0067] In this comparative example, different from Example 6, the adhesive prepared in Comparative Example 1 was used to replace the adhesive prepared in Example 2, and the rest was the same as Example 6.

[0068] The demoulding force of Examples 5 and 6 and Comparative Examples 2 and 3 and the flexural strength of the embryos (undefatted embryos) were tested (referring to ASTM D790). The results are shown in Table 1.

[0069] Table 1:

[0070]

[0071] analyze:

[0072] Comparing Example 6 with Comparative Example 3, and comparing Example 5 with Comparative Example 2, it can be seen that the adhesive for powder injection molding process provided by the present invention can make the injection blank have good molding performance, and the injection blank has good mechanical strength.

[0073] Comparing Example 5 with Example 6, and Comparative Example 2 with Comparative Example 3, it can be seen that the coated mold facilitates demolding and improves the quality of the embryo. The mold coating has a low surface energy, which reduces adhesion, friction, and interfacial residual stress, thereby reducing demolding force and flash. It also improves demolding quality, preventing structural damage or defects in the embryo during demolding, thereby enhancing the mechanical strength of the embryo.

[0074] In summary, the above specific embodiments and comparative examples are only for the purpose of clearly illustrating the present invention and are not to be construed as limiting the present invention. It should be understood by those skilled in the art that, without departing from the spirit and scope of the present invention, various equivalent substitutions, modifications, changes or improvements may be made to the technical solutions of the present invention and their implementations, and that these changes or improvements are all within the scope of the present invention. The scope of protection of the present invention shall be subject to the appended claims.

Claims

1. An adhesive for powder injection molding process, characterized in that, The invention is prepared from the following raw materials in parts by weight: 20-23 parts of paraffin wax, 5-8 parts of stearic acid, 15-20 parts of polyethylene glycol, 10-15 parts of polydimethylsiloxane, 25-30 parts of ethyl acetate solution, and 10-15 parts of modified bisphenol A epoxy resin; wherein the modified bisphenol A epoxy resin is prepared from methoxy polyethylene glycol amine and bisphenol A epoxy resin; and the preparation method of the modified bisphenol A epoxy resin comprises the following steps: The bisphenol A epoxy resin is heated and melted, and then methoxy polyethylene glycol amine and a catalyst are added, and the mixture is heated and reacted under a nitrogen atmosphere. After the reaction, the mixture is cooled to room temperature and washed to obtain a modified bisphenol A epoxy resin; The heating temperature of the blend is 100-150°C, the mass ratio of bisphenol A epoxy resin and methoxy polyethylene glycol amine is 3-9:1, the catalyst includes tetraisopropyl titanate, the reaction is carried out under N2 atmosphere for 5-10 hours, the bisphenol A epoxy resin includes DGEBA, and the molecular weight of methoxy polyethylene glycol amine is 2000.

2. The method for preparing an adhesive for powder injection molding according to claim 1, characterized in that: The steps include: Weigh each component by weight, add paraffin wax to the polyethylene glycol solution, mix well, add stearic acid, heat and stir to obtain a mixed solution 1; Adding polydimethylsiloxane and modified bisphenol A epoxy resin into ethyl acetate solution, mixing evenly, and then heating and stirring to obtain a second mixed solution; The mixed solution 1 and the mixed solution 2 are mixed, heated and stirred, discharged, cooled, and filtered to obtain an adhesive for powder injection molding technology.

3. The method for preparing an adhesive for powder injection molding according to claim 2, characterized in that: The heating temperature is 80-110°C and the stirring time is 1-6h.

4. An adhesive for use in a powder injection molding process, wherein the adhesive is prepared by the adhesive for use in a powder injection molding process according to claim 1 or the method for preparing an adhesive for use in a powder injection molding process according to claim 2, characterized in that: The steps include: The metal powder is mixed with the binder to obtain the feed material, which is then granulated and then injection molded. The mold is preheated first, the feed material is injected into the mold, and the mold is integrally formed. After cooling, the mold is demolded to obtain a blank. The blank is degreased, sintered, and cooled to obtain a formed blank.

5. The adhesive according to claim 4 is used in a powder injection molding process, characterized in that: The mold may be a mold with or without a coating, and the coating is formed by a coating liquid. The preparation method of the coating liquid comprises the following steps: adding TEOS to anhydrous ethanol, adding deionized water dropwise, and adjusting the pH to 4-5; stirring the mixture to react to obtain a sol liquid; diluting the fluoroamide silane monomer and the aminosilane oligomer with isopropyl alcohol; then adding a surfactant and performing ultrasonic dispersion; Add the sol solution while stirring, and finally add the organic metal catalyst and stir evenly to obtain the coating solution.

6. The adhesive according to claim 5 is used in a powder injection molding process, characterized in that: The preparation method of the fluoroamide silane monomer comprises the following steps: dissolving APTES in anhydrous THF, cooling in an ice bath to 0-5°C, adding tetrafluorosuccinyl chloride dropwise while maintaining the temperature at ≤10°C, continuously stirring after the addition is completed, then adding triethylamine dropwise, heating and stirring to obtain a reaction liquid, extracting the reaction liquid, drying the organic phase, filtering, and performing reduced pressure rotary evaporation to obtain the fluoroamide silane monomer.

7. The adhesive according to claim 5 is used in a powder injection molding process, characterized in that: The surfactant includes an organosilicon surfactant, the organometallic catalyst includes an organobismuth catalyst and an organotin catalyst, and the organotin catalyst includes at least one of dibutyltin dilaurate and dibutyltin diacetate.

8. The adhesive according to claim 5 is used in a powder injection molding process, characterized in that: The coating is formed by a coating liquid, which is sprayed or brushed on the area where the mold will be demoulded later. The coating thickness is controlled to be 3-5μm, and the coating is left to dry. The mold is then placed in a heating box at 100-150° C. for heat preservation; the temperature is then slowly raised to 150-200° C. and then kept warm to obtain a mold containing a coating.

Citation Information

Patent Citations

  • Ultra-low-viscosity binder for three-dimensional spray molding process and preparation method of ultra-low-viscosity binder

    CN116285227A

  • Preparation method of soft and hard composite anti-icing coating with low icing adhesion

    CN119410231A